Publishing Multi-Purpose Data Sets from KM3NeT - Schnabel, Jutta (CEUR Workshop Proceedings, 2020)
The KM3NeT neutrino detector, a water Cherenkov experiment to detect relativistic charged particles, is currently under construction at two deep-sea locations in the Mediterranean Sea. As crossdomain experiment between neutrino, astro-particle and astrophysics, data processing and data publication from KM3NeT draws on computing paradigms and standardization from all fields. In this contribution, key considerations for the provision of multi-purpose open data sets, interface options and interoperability requirements are presented.
CRIS-Team Scopus Importer:2021-04-19
Keywords: KM3NeT; neutrino astronomy; neutrino physics; open data